Ancient roots for polymorphism at the HLA-DQ alpha locus in primates. - Gyllensten, U B (1989)
The genes encoding the human histocompatibility antigens (HLA) exhibit a remarkable degree of polymorphism as revealed by immunologic and molecular analyses. This extensive sequence polymorphism either may have been generated during the lifetime of the human species or could have arisen before speciation and been maintained in the contemporary human population by selection or, possibly, by genetic drift. These two hypotheses were examined using the polymerase chain reaction method to amplify polymorphic sequences from the DQ alpha locus, as well as the DX alpha locus, an homologous but nonexpressed locus, in a series of primates that diverged at known times. In general, the amino acid sequence of a specific human DQ alpha allelic type is more closely related to its chimpanzee or gorilla counterpart than to other human DQ alpha alleles. Phylogenetic analysis of the silent nucleotide position changes shows that the similarity of allelic types between species is due to common ancestry rather than convergent evolution. Thus, most of the polymorphism at the DQ alpha locus in the human species was already present at least 5 million years ago in the ancestral species that gave rise to the chimpanzee, gorilla, and human lineages. However, one of the DQ alpha alleles may have arisen after speciation by recombination between two ancestral alleles.